COMPARING THE RETURN ON MUDHARABAH DEPOSIT AND THE RETURN ON EQUITY: ASSESSING THE FAIRNESS IN INDONESIAN ISLAMIC BANKING INDUSTRY - Nurul Fadhilah; Achmad Tohirin (Department of Islamic Banking, Faculty of Islamic Economics and Business, IAIN Sultan Amai Gorontalo, 2021)
Abstract This paper compared the return on mudharabah deposit (ROMD) and the return on equity (ROE) in Indonesian Islamic banks to unveil the differences and factors that affect them. The purpose of this paper is to evaluate the profit and loss sharing mechanism in Islamic banking through the return on mudharabah deposit and on equity. The quarterly financial report from 10 Islamic banks within the period of 2011 to 2016 are processed using independent t-test to compare means and panel regression method to disclose the variables affecting the behavior of ROMD and ROE. The results show that the ROMD and ROE are statistically different, with ROMD tend to be lesser than ROE. It also found that ROA, total equity/total asset, total total deposit/total asset, total financing/total asset, bank size and total of mudharabah deposit accounts are affect the variability of ROMD, and the same variables,exclude the mudharabah deposit account, affect the ROE. Following this result, Islamic banks in Indonesia need to evaluate the governance to treat the mudharabah contract as a mode of equity participation in nature, as like as the contract with the shareholders, in order to comply with Islamic economic framework through the presence of the fairness in banking business.